Millennial experiences of middle-class precarity and opportunities for agency - Lim, Gladys Wan Chan (2019)
Recent trends suggest that precarity has expanded to the centre of society, resulting in what has been noted as the “middle-class squeeze” in many developed societies today. Yet, existing literature on precarity in Singapore continues to focus only on the experiences of the most exploited. By employing a broader definition of the precariat, this study seeks to understand the experiences of middle-class millennial Singaporeans in navigating the “middle-class squeeze”, as well as how factors contributing to this phenomenon may be similar to or differ from those affecting the working class. Findings from 17 semi-structured in-depth interviews and secondary research reveal how factors such as economic restructuring and intensifying foreign competition have fuelled middle-class anxieties about employment and financial security alongside one’s aspirations for the future. In addition, findings also inform about the possibilities for and ways in which Singapore’s middle class may exercise individual agency in this age of precarity.